Comparing Different Thermal Runaway Triggers for Two Automotive Lithium-Ion Battery Cell Types. Issue 13 (14th October 2020) - Essl, C.; Golubkov, A. W.; Fuchs, A.
Abstract : In order to understand the lithium-ion battery (LIB) failing behavior and to prevent failures and their consequences, different LIB safety tests, also called abuse tests, have been developed. This paper focuses on thermal runway (TR) triggered by overtemperature, overcharge and nail-penetration. It shows the setup and the results of the three different TR triggers on two different cell types in a custom-made TR reactor. The investigated cell types are state-of-the-art automotive pouch and hard case cells. The results are discussed in three main categories: thermal behavior, vent gas production and vent gas composition. The results and findings are supposed to be valuable for battery pack designer, car manufacturer and testing institutions for the development of future battery testing facilities and regulations.